1994
DOI: 10.1063/1.111982
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of porous silicon superlattices

Abstract: Porous silicon superlattices have been fabricated electrochemically. The current was monitored periodically during the electrolysis and samples were made with several periods. They have been investigated using reflectance measurements in the infrared and visible range. We demonstrate that porous silicon superlattices act like a multilayer dielectric device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
112
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(115 citation statements)
references
References 8 publications
1
112
0
2
Order By: Relevance
“…Depending on several parameters such as Si wafer dopant type and resistivity, current density, and electrolyte composition, a wie range of pore sizes and morphologies can be obtained. 14,15 In addition, the pore diameters can be systematically varied in either horizontal or vertical directions (relative to the wafer surface), leading to pore gradient 11-13 and multilayer [16][17][18] structures.…”
mentioning
confidence: 99%
“…Depending on several parameters such as Si wafer dopant type and resistivity, current density, and electrolyte composition, a wie range of pore sizes and morphologies can be obtained. 14,15 In addition, the pore diameters can be systematically varied in either horizontal or vertical directions (relative to the wafer surface), leading to pore gradient 11-13 and multilayer [16][17][18] structures.…”
mentioning
confidence: 99%
“…The thickness of each "layer" is determined by the etching time. A periodical switching between two distinct current densities will produce porosity multilayers with a varied refractive index profile [24]. These multilayers are able to exhibit a photonic band gap, preventing light propagation at a range of frequencies due [31,32].…”
Section: Optical Properties Of Porous Siliconmentioning
confidence: 99%
“…Therefore, the optical properties can periodically vary with depth in the porous superlattice layer. Such structures have been applied for waveguides, microcavity and distributed Bragg reflectors [14,15]. It has been also demonstrated that these devices can be used as sensors for various type of chemical species and DNA [15,18 -20] since a filling of the pores with dielectric substances modifies the average refractive index of each layer and thus can change the optical response of the superlattice.…”
Section: Introductionmentioning
confidence: 99%